Pengaruh Total Asset Turnover, Debt to Equity Ratio, dan Return on Assets terhadap Manajemen Laba pada Perusahaan Pertambangan di BEI Periode 2020–2024 - Saraswati, Novi; Fathihani (STKIP MAJENANG, 2025)
This study analyzes the effect of Total Asset Turnover, Debt to Equity Ratio, and Return on Assets on earnings management in mining companies listed on the Indonesia Stock Exchange during 2020–2024. Using a quantitative and causal research design, the study examines 18 purposively selected companies over five years, resulting in 90 observations. Data were analyzed through panel data regression using SPSS 26. The results show that Total Asset Turnover does not significantly affect earnings management, while Debt to Equity Ratio and Return on Assets have a significant influence. These findings indicate that profitability and leverage play important roles in shaping earnings management practices in the mining sector